Do exporters really pay higher wages?: First evidence from German linked employer-employee data - Thorsten Schank; Claus Schnabel; Joachim Wagner (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2006)
Many plant-level studies find that average wages in exporting firms are higher than in non-exporting firms from the same industry and region. This paper uses a large set of linked employer-employee data from Germany to analyze this exporter wage premium. We show that the wage differential becomes smaller but does not completely vanish when observable and unobservable characteristics of the employees and of the workplace are controlled for. For example, blue-collar (white-collar) employees working in a plant with an export-sales ratio of 60 percent earn about 1.8 (0.9) percent more than similar employees in otherwise identical nonexporting plants.
Keywords: F10; D21; L60; 330; Lohnstruktur; Exportindustrie; Verarbeitendes Gewerbe; Vergleich; Schätzung; Deutschland